Natural course of non-surgical acute traumatic subdural hematomas: Retrospective analysis of 92 patients (Annals of Medical Research, 2021)
Aim: In the present study, we aimed todiscuss the natural course of acute subdural hematoma (ASDH) patients who were not operated according to the admisssion findings.Material and Methods: In this study patients who admittedwith a diagnosis of traumatic ASDH and underwent conservative treatment according to the admission findings at the neurosurgery clinic of Adıyaman University between 2013 and April 2019 were identified. Patients who had a diagnosis of ASDH less than 10 mm, a midline shift of less than 5 mm and had a repeat computed tomography (CT) scan were included in this study.Two groups were formed with and without increase in the hematoma size according to thecontrol CT. Age, gender, anticoagulation status, comorbidities of the patients, type of trauma, size of the hematoma, GCS scores and presence or absence of a “low-density band” on CT were evaluated. Results: We identified 92 patients who had coded as “traumatic ASDH” and managed nonoperatively according to the findings of the initial CT.32.6% of patients had hematoma growth according to the control CT and68.4% had either decreased or the same size.According to the statistical analysis results, anticoagulant drug use(p=0.001) and comorbidity status(p=0.03) were found to be related with the increase of the hematoma size. Also there was no statistically significant difference (p=0.07) between the two groups about the low density band but it was seen more differencein the non-increased group. Conclusion: Conservative treatment is one of the treatment methods of traumatic acute subdural hematomas. Patients who have under 10 mm hematoma size and 5mm midline shift can be followed up by non-surgical methods. But increased headache in these patients may be a sign that should be considered in terms of increased hematoma. Furthermore, the use of anti-coagulant drugs and the presence of comorbidity make patients more risky.
Keywords: Acute subdural hematoma; trauma; low density band; anticoagulation; comorbidity.